2013
DOI: 10.1159/000346794
|View full text |Cite
|
Sign up to set email alerts
|

TRAF2 is Upregulated in Relapsing-Remitting Multiple Sclerosis

Abstract: Objective: To elucidate the role of tumor necrosis factor (TNF) receptor signal transduction in multiple sclerosis (MS). Methods: We performed a cross-sectional analysis of the gene expression of TRAF2 (TNF receptor-associated factor 2) and RIP (receptor-interacting protein) in peripheral blood leukocytes of 23 relapsing-remitting (RR), 19 secondary progressive (SP) and 12 primary progressive (PP) MS patients as well as of 29 healthy controls by quantitative RT-PCR. Additionally, we monitored a subgroup of 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In human, both down- and up-regulated expression of TRAF2 has been detected in peripheral blood mononuclear cells (PBMCs) of patients with systemic lupus erythematosus (SLE) [92,93]. TRAF2 expression is elevated in PBMCs of patients with RA and relapsing-remitting multiple sclerosis (MS) [94,95]. Studies of mouse models revealed the critical role of TRAF2 in regulating T cell homeostasis and T cell tolerance, which are essential for controlling autoimmune inflammatory diseases.…”
Section: Traf2mentioning
confidence: 99%
“…In human, both down- and up-regulated expression of TRAF2 has been detected in peripheral blood mononuclear cells (PBMCs) of patients with systemic lupus erythematosus (SLE) [92,93]. TRAF2 expression is elevated in PBMCs of patients with RA and relapsing-remitting multiple sclerosis (MS) [94,95]. Studies of mouse models revealed the critical role of TRAF2 in regulating T cell homeostasis and T cell tolerance, which are essential for controlling autoimmune inflammatory diseases.…”
Section: Traf2mentioning
confidence: 99%
“…TRAF2 expression in peripheral blood leukocytes was significantly elevated in RR MS patients compared to the other disease courses and healthy persons, and RIP expression was significantly elevated in the patient groups compared to healthy controls, which might be interpreted as the molecular equivalent of an elevated general inflammatory activity in MS patients compared to healthy individuals [20]. …”
Section: Discussionmentioning
confidence: 99%
“…TRAF2 (TNF receptor-associated factor 2) gene expression was increased in leukocytes of RRMS patients compared to other MS forms and healthy controls. In addition, RIP (receptor-interacting protein) expression was elevated in peripheral blood leukocytes of RRMS, SPMS and PPMS patients compared to healthy controls [67].…”
Section: Tnfα and Il-17 Pathways In Multiple Sclerosismentioning
confidence: 97%
“…TNFα adapter proteins ↑ FADD mRNA in leukocytes [66] ↑TRAF2 mRNA in leukocytes [67] ↓TRADD, FADD, RIP-1, TRAF-2 mRNA in PBMC [123] expression. Some kinds of dysregulation in cell functioning can be common in different autoimmune diseases.…”
Section: Smad7mentioning
confidence: 99%